Variations of thunderstorm patterns on the territory of Ukraine in the ХХ and at the beginning of the ХХІ century - Мацук, Ю. М. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2013)
Research of the spatial-temporal distribution and repeatability of thunder-storms on the territory of Ukraine for the periods of 1936-1965 and 1973-2012 are presented. Spatial distribution of storm patterns on the territories of Ukraine depends on orographical heterogeneity and air temperature conditions which promote the formation of powerful ascending air movements and cold fronts aggravation. The analysis of an average number of days with thunder-storms across Ukraine has revealed the maximum in the area of the Carpathians and has shown that an intensive storm depends on the orientation of mountain ridges in relation to the prevailing streams, height of slopes and their security. A significant reduction in the number of days with thunderstorms in the second period is revealed. General dynamics in the storm variations for the period of 1970-2012 shows a gradual steady increase in the number of days with thunderstorms.